Magnetic core and preparation method and application thereof

A two-step heat treatment and magnetic field process for amorphous magnetic cores addresses uneven grain growth, enhancing magnetic permeability across frequencies, particularly at low frequencies, by inducing nanocrystallization and grain homogenization.

CN119252641APending Publication Date: 2025-01-03FOSHAN CITY ZHONGYAN AMORPHOUS TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411588561.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Conventional heat treatment methods for amorphous magnetic cores result in incomplete grain precipitation, uneven grain growth, and reduced magnetic permeability, especially at low frequencies, limiting the magnetic core's performance across different frequency bands.

Method used

A two-step heat treatment process at specific pressures and temperatures followed by magnetic field heat treatment to induce nanocrystallization and grain homogenization, ensuring uniform grain growth and orientation, thereby enhancing magnetic permeability across a wide frequency range.

Benefits of technology

The method achieves magnetic permeability greater than 250,000 at 1 kHz, 100,000-139,000 at 10 kHz, and 17,000-34,000 at 100 kHz, significantly improving the magnetic core's performance compared to conventional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252641A_ABST
    Figure CN119252641A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of magnetic materials, and particularly discloses a magnetic core and a preparation method and application thereof. According to the method disclosed by the invention, the amorphous magnetic core is induced to realize nanocrystallization and grain homogenization through two times of heat treatment at certain pressure and temperature and then magnetic field heat treatment at specific temperature, so that the problems of nonuniform nucleation and excessive growth of nanocrystals in conventional heat treatment are effectively solved; the magnetic conductivity of the magnetic core under different frequencies is comprehensively improved, the purpose of improving the magnetic conductivity of the full-band magnetic core to the maximum extent is achieved, especially under the low frequency of 1 kHz, the effective magnetic conductivity of the magnetic core is larger than 250,000, and the defect that the magnetic conductivity of the low-band magnetic core is low is effectively overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnetic materials, and in particular relates to a magnetic core and a preparation method and application thereof. Background Art

[0002] Iron-based amorphous / nanocrystalline soft magnetic alloys are usually made of amorphous strips by high-speed copper roller rapid cooling process, and the amorphous strips are wound into amorphous cores. Amorphous cores generally need to undergo appropriate heat treatment processes to finely control the microstructure of the alloy, that is, a single magnetic α-Fe phase is precipitated on the amorphous matrix and transformed into a dual-phase coexistence structure of amorphous and nanocrystalline to form a magnetic core. This special dual-phase nanostructure is also the main reason why the magnetic core exhibits excellent comprehensive soft magnetic properties. Therefore, the heat treatment process of the magnetic core plays a decisive role in obtaining high-performance magnetic cores.

[0003] In conventional heat treatment methods for amorphous magnetic cores, such as annealing in an atmosphere furnace, amorphous magnetic cores often experience incomplete grain precipitation, uneven grain precipitation, and excessive growth under high-temperature heat treatment. All of the above conditions will deteriorate the performance of the obtained magnetic core, especially significantly reduce the magnetic permeability of the magnetic core. Moreover, the magnetic permeability is different at different frequencies, resulting in different degrees of improvement in the magnetic permeability of the heat treatment process at different frequency bands. Therefore, general magnetic cores cannot maintain the highest magnetic permeability at different frequency bands, especially at low frequencies, such as 1kHz, the effective magnetic permeability of existing magnetic cores is generally as low as 50,000 or less, and at 100kHz, the effective magnetic permeability of the magnetic core is generally as low as 10,000 or less. Therefore, the heat treatment process based on the existing technology has great limitations on improving the magnetic permeability of the magnetic core, and it is urgent to develop a new magnetic core preparation technology to improve the magnetic permeability of the magnetic core to the greatest extent possible. Summary of the invention

[0004] In view of the limitations of the heat treatment process in the prior art on improving the magnetic permeability of the magnetic core, the present invention provides a magnetic core and a preparation method and application thereof.

[0005] To achieve the above purpose, the following technical solutions are specifically included:

[0006] A method for preparing a magnetic core comprises the following steps:

[0007] (1) subjecting the amorphous magnetic core to a first heat treatment and a second heat treatment in sequence, cooling and reducing the pressure to obtain a pre-burned magnetic core; the temperature of the first heat treatment is 400-480° C., the temperature of the second heat treatment is 490-540° C.; the pressure of the first heat treatment is 10-40 MPa, and the pressure of the second heat treatment is 20-80 MPa;

[0008] (2) The pre-burned magnetic core is subjected to magnetic field heat treatment and cooled to obtain the magnetic core.

[0009] In the method of the present invention, two heat treatments are first performed at a certain pressure and temperature, and then a magnetic field heat treatment is performed at a specific temperature, so as to induce the amorphous magnetic core to achieve nanocrystallization and homogenization of the grains, effectively solving the problems of uneven nucleation and excessive growth of nanocrystals in conventional heat treatment, comprehensively improving the magnetic permeability of the magnetic core at different frequencies, and achieving the purpose of maximizing the magnetic permeability of the magnetic core in the full frequency band, especially at a low frequency of 1kHz, the effective magnetic permeability of the magnetic core is greater than 250,000, effectively solving the defect of low magnetic permeability of the magnetic core in the low frequency band.

[0010] Preferably, in step (1), the time of the first heat treatment is 70-180 min, and the heating rate of the first heat treatment is 1-30° C. / min.

[0011] Preferably, the time of the second heat treatment is 70-180 min, the heating rate of the second heat treatment is 1-5° C. / min, and the cooling rate is 5-200° C. / min.

[0012] In the method of the present invention, in step (1), the first heat treatment and the second heat treatment are mainly aimed at crystallizing the amorphous magnetic core, aiming to promote the precipitation of a large number of fine α-Fe nano-grains on the amorphous matrix; in step (2), the grains in the magnetic core are induced to grow in an oriented manner along the direction of the magnetic field through the action of the magnetic field while precipitating and growing, and appropriate magnetic anisotropy is introduced under the action of the external magnetic field; therefore, the precipitation, size and growth orientation of nano-grains are regulated by the method of the present invention, thereby improving the comprehensive soft magnetic properties of the obtained nanocrystalline magnetic core.

[0013] Preferably, in step (1), the pressurization methods of the first heat treatment and the second heat treatment are each selected from at least one of pressurization by inert gas pressure and pressurization by mold extrusion; the amorphous magnetic core in step (1) is formed by winding an amorphous strip, and the magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the amorphous magnetic core.

[0014] Preferably, in step (1), the amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%.

[0015] Further preferably, the amorphous magnetic core comprises Fe 73.5 Si 15.5 B7Cu1Nb3、Fe 73.5 Si 13.5 B9Cu1Nb3、Fe 63.5 Ni 10 Si 15.5B7Cu1Nb3、Fe 63.5 Co5Ni5Si 15.5 B7Cu1Nb3、Fe 68.5 Co5Si 15.5 At least one of B7Cu1Nb3.

[0016] The method of the invention is applicable to iron-based amorphous magnetic cores of different compositions, especially amorphous magnetic cores of the above-mentioned compositions, and can obtain magnetic cores with low frequency and high magnetic permeability.

[0017] Preferably, in step (1), the cooling and depressurization is carried out by first naturally cooling the system to below 200°C and then releasing the pressure of the system to atmospheric pressure, with a cooling rate of 10-500°C / min.

[0018] Preferably, in step (2), the temperature of the magnetic field heat treatment is 350-450° C., the time of the magnetic field heat treatment is 10-90 min, and the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.

[0019] Preferably, in step (2), the rate of heating to the magnetic field heat treatment temperature is 1-20°C / min.

[0020] Preferably, in step (2), the cooling method is natural cooling.

[0021] Preferably, the magnetic permeability of the magnetic core is greater than or equal to 25,000.

[0022] Further preferably, at a frequency of 1 kHz, the magnetic permeability of the magnetic core is 250,000-350,000, at a frequency of 10 kHz, the magnetic permeability of the magnetic core is 100,000-139,000, and at a frequency of 100 kHz, the magnetic permeability of the magnetic core is 17,000-34,000.

[0023] Further preferably, the magnetic core contains nano-sized α-Fe grains.

[0024] The present invention also provides an application of the magnetic core in the preparation of new energy vehicles, photovoltaic energy storage equipment, electronic information, and mobile communications. The magnetic core of the present invention has a high magnetic permeability and is more suitable for use in the preparation of the above-mentioned equipment.

[0025] Compared with the prior art, the present invention has the following beneficial effects: first, through two heat treatments at a certain pressure and temperature, and then through a magnetic field heat treatment at a specific temperature, the amorphous magnetic core is induced to achieve nanocrystallization and grain homogenization, which effectively solves the problems of uneven nucleation and excessive growth of nano-grains in conventional heat treatment, and comprehensively improves the magnetic permeability of the magnetic core at different frequencies, so as to achieve the purpose of maximizing the magnetic permeability of the magnetic core in the full frequency band, especially at a low frequency of 1kHz, the effective magnetic permeability of the magnetic core is greater than 250,000, which effectively solves the defect of low magnetic permeability of the magnetic core in the low frequency band. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 For homemade Fe 73.5 Si 15.5 X-ray diffraction (XRD) pattern of B7Cu1Nb3 amorphous ribbon.

[0027] Figure 2 It is a comparison diagram of the magnetic domain structure between Example 1 (left figure) and Comparative Example 4 (right figure).

[0028] Figure 3 This is a physical picture of the magnetic core prepared in Example 1.

[0029] Figure 4 Graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of Examples 1 to 13.

[0030] Figure 5 This is a graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of comparative examples 1 to 5. DETAILED DESCRIPTION

[0031] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0032] The amorphous strips used in the following embodiments and comparative examples can be obtained by commercial methods or by conventional methods. The homemade methods may include the following processes: (1) component proportioning; (2) master alloy smelting; and (3) obtaining the corresponding amorphous strips by strip spinning and strip winding.

[0033] Example 1

[0034] (1) The alloy Fe in atomic percentage 73.5 Si 15.5 B7Cu1Nb3 amorphous strip (self-made, XRD results as attached Figure 1) is wound into an amorphous magnetic core, and then the amorphous magnetic core is placed in a gas furnace body, evacuated, filled with inert gas argon gas so that the system has a certain gas pressure, heated to a first heat treatment temperature of 430° C. at a heating rate of 15° C. / min, and at the same time, argon gas is continuously filled to pressurize to a first heat treatment pressure of 30 MPa, and the temperature and pressure are maintained for 90 minutes;

[0035] (2) Continue to increase the temperature and pressurize, and continue to heat to the second heat treatment temperature of 510°C at a heating rate of 3°C / min, and at the same time maintain the second heat treatment pressure of 70MPa, and keep the temperature and pressure at this temperature and pressure for 90min; then cool down to below 200°C, start to release the pressure to room pressure, and set the cooling rate to natural cooling with the furnace to obtain a pre-burned magnetic core;

[0036] (2) Magnetic field heat treatment: The pre-burned magnetic core is placed in the magnetic field heat treatment furnace and heated to 400°C at a heating rate of 10°C / min. At this time, a magnetic field parallel to the width direction of the amorphous strip is added, and the magnetic field intensity is 1500Gs. The magnetic field heat treatment is carried out at this temperature and magnetic field for 90 minutes, and the temperature is cooled to room temperature with the furnace to obtain a magnetic core.

[0037] Examples 2-12 and Comparative Examples 1-5

[0038] The only difference between Examples 2-12 and Comparative Examples 1-5 and Example 1 is: in steps (1)-(3), the heating rate and / or temperature and / or pressure of the first heat treatment, the heating rate and / or temperature and / or pressure of the second heat treatment, the magnetic field heat treatment temperature and / or magnetic field intensity and / or time. The detailed differences are shown in Table 1.

[0039] Example 13

[0040] The difference between the embodiment and the embodiment 1 is that in step (1), the amorphous strip is Fe in atomic percentage. 73.5 Si 13.5 B9Cu1Nb3.

[0041] Table 1

[0042]

[0043]

[0044] The performance of the magnetic core prepared above was tested: the inductance L of the magnetic core was tested using a Keysight Agilent 4294A precision impedance analyzer in an external magnetic field of 1A / m and a frequency range of 1kHz to 100kHz; the effective magnetic permeability μ e Obtained through the inductance L conversion formula:

[0045] μe =(L×L e ) / (N 2 ×A e ),

[0046] Where, L is the core inductance, μ e is the effective magnetic permeability of the core, L e is the magnetic path length of the core, A e is the effective cross-sectional area of ​​the core, N is the number of coil turns (the test condition is 1 turn), and the test results are shown in Table 2.

[0047] Conventional heat treatment process is the preparation method in Comparative Example 4. Now, the magnetic core prepared in Comparative Example 4 is used as a basis for comparison to calculate the change rate X of the magnetic permeability of the magnetic core of other embodiments of the present invention and the conventional heat treatment process Comparative Example 4: X f =(μ n -μ 对比例4 ) / μ 对比例4 *100%, where μ n Refers to the effective magnetic permeability of a magnetic core obtained in a certain embodiment or comparative example at frequency f, μ 对比例4 Refers to the effective magnetic permeability of the magnetic core prepared in Comparative Example 4 at frequency f, and the results are shown in Table 2.

[0048] Table 2

[0049]

[0050]

[0051] In conventional heat treatment, the sample will be heated unevenly, resulting in uneven nucleation of nanocrystals, incomplete precipitation of grains and excessive growth, which makes the effective magnetic permeability of the magnetic core low. Figure 2 (right) and Figure 5 As shown in Table 2, its magnetic permeability is low. Figure 2 and 4-5 Analysis of Examples 1-13 and Comparative Example 4 shows that the present invention first performs the first heat treatment to make the amorphous magnetic core evenly heated, providing a basis for the second heat treatment; then the temperature is raised to the second heat treatment temperature, and a slow heating rate is used, and a suitable holding time is selected to ensure that the grains have enough time to precipitate at a relatively high temperature, and grow slowly and evenly under the action of air pressure, avoiding uneven heating caused by overheating, or incomplete grain precipitation due to too short a time, or excessive grain growth due to too long a holding time; finally, combined with magnetic field heat treatment, the nano-grains are completely turned, and the force field heat treatment and magnetic field heat treatment as a whole make the grains in the magnetic core precipitate completely and have uniform size. The method of the present invention can comprehensively improve the comprehensive electromagnetic properties of the magnetic core, obtain low-frequency high magnetic permeability and high-frequency high magnetic permeability, respectively, and achieve the purpose of improving the full-band magnetic permeability of the magnetic core. Under the condition of frequency 1kHz, the magnetic permeability of the magnetic core of the present invention is 250,000-350,000, and the effective magnetic permeability is increased by more than 70% compared with the conventional heat treatment method of comparative example 4; under the condition of 10kHz, the magnetic permeability of the magnetic core of the present invention is 100,000-139,000, and the effective magnetic permeability is increased by more than 30% compared with the conventional heat treatment method of comparative example 4; under the condition of 100kHz, the magnetic permeability of the magnetic core of the present invention is 17,000-34,000, and the effective magnetic permeability is increased by more than 20% compared with the conventional heat treatment method of comparative example 4. In addition, combined with the analysis of comparative examples 1-3 and 5, it can be seen that without performing two heat treatments, the heat treatment temperature is too low or too high, the pressure is too low or too high, and the lack of magnetic field heat treatment cannot effectively improve the effective magnetic permeability of the magnetic core in the frequency range of 1-100kHz at the same time.

[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a magnetic core, characterized in that: The steps include: (1) subjecting the amorphous magnetic core to a first heat treatment and a second heat treatment in sequence, cooling and reducing the pressure to obtain a pre-burned magnetic core; the temperature of the first heat treatment is 400-480° C., the temperature of the second heat treatment is 490-540° C.; the pressure of the first heat treatment is 10-40 MPa, and the pressure of the second heat treatment is 20-80 MPa; (2) The pre-burned magnetic core is subjected to magnetic field heat treatment and cooled to obtain the magnetic core.

2. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the time of the first heat treatment is 70-180 min, and the heating rate of the first heat treatment is 1-30° C. / min.

3. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the time of the second heat treatment is 70-180 min, the heating rate of the second heat treatment is 1-5°C / min, and the cooling rate is 5-200°C / min.

4. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the pressurization methods of the first heat treatment and the second heat treatment are each selected from at least one of pressurization by inert gas pressure and pressurization by mold extrusion; in step (1), the amorphous magnetic core is formed by winding an amorphous strip, and in step (2), the magnetic field direction of the magnetic field heat treatment is parallel to the width direction of the amorphous magnetic core.

5. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%.

6. The method for preparing a magnetic core according to claim 1, characterized in that: In step (2), the temperature of the magnetic field heat treatment is 350-450°C, the time of the magnetic field heat treatment is 10-90 minutes, and the magnetic field intensity of the magnetic field heat treatment is 800-3000Gs.

7. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the cooling and depressurization method is to first naturally cool the system to below 200° C. and then release the pressure of the system to atmospheric pressure; in step (2), the cooling method is natural cooling.

8. A magnetic core made by the method for making a magnetic core according to any one of claims 1 to 7.

9. The magnetic core according to claim 8, characterized in that At a frequency of 1kHz, the magnetic permeability of the magnetic core is 250,000-350,000, at a frequency of 10kHz, the magnetic permeability of the magnetic core is 100,000-139,000, and at a frequency of 100kHz, the magnetic permeability of the magnetic core is 17,000-34,000.

10. Use of the magnetic core according to claim 8 or 9 in the preparation of new energy vehicles, photovoltaic energy storage equipment, electronic information, and mobile communications.

Citation Information

Cited By

  • Magnetic core, preparation method therefor and use thereof

    WO2026097696A1